2010
DOI: 10.1007/s00404-010-1447-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between tobacco use in pregnancy and placenta-associated syndromes: a population-based study

Abstract: Maternal smoking in pregnancy is a risk factor for the development of placenta-associated syndrome. Smoking cessation interventions in pregnancy should continue to be encouraged in all maternity care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 27 publications
2
37
2
7
Order By: Relevance
“…Large population-based studies reported that the risk of stillbirth is twice as high in African women, compared to Caucasians [16,18], the risk increases with maternal weight [19,20,21], and it is higher in smokers than non-smokers [22] and in pregnancies conceived by in vitro fertilization and ovulation induction than in spontaneous conceptions [23]. A systematic review examining the causes of stillbirth reported that chronic hypertension is associated with an increased risk with odds ratios of 1.5–2.7 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Large population-based studies reported that the risk of stillbirth is twice as high in African women, compared to Caucasians [16,18], the risk increases with maternal weight [19,20,21], and it is higher in smokers than non-smokers [22] and in pregnancies conceived by in vitro fertilization and ovulation induction than in spontaneous conceptions [23]. A systematic review examining the causes of stillbirth reported that chronic hypertension is associated with an increased risk with odds ratios of 1.5–2.7 [24].…”
Section: Discussionmentioning
confidence: 99%
“…It was considered whether adjusted ORs for preterm birth, stillbirth, placental abruption and SGA were consistent with findings from other Australian and international population-based studies that used routinely collected data sources or longitudinal cohort data. 1,[42][43][44][45][46][47][48] All analyses were carried out in SAS version 9.3. Ethical approval for this study was granted by the NSW Population and Health Services Research Ethics Committee.…”
Section: Impact Of Enhanced Identificationmentioning
confidence: 99%
“…Functionally, these modifications appear to alter placental blood flow [10], and disturb progesterone production [11], estrogen metabolism [12], amino acid transport [13], as well as the activity of drug-metabolizing enzymes [14]. It is worth noting that CSE during pregnancy is also associated with increased risks of placenta-associated syndromes [15], such as preterm birth, placenta previa and placental abruption [16,17].…”
Section: Introductionmentioning
confidence: 99%